KITAB KUNING DAN KONSTRUKSI NALAR PESANTREN - Muhammad Ardiansyah (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
The various challenges faced by pesantren, especially those related to the development of scientific studies in the context of answering contemporary problems of Muslims in Indonesia. The issues of human rights (HAM), gender, and nationalism, for example, are a big challenge for pesantren to answer and solve this national problem. However, if the pesantren only relies on classical literature, let alone the traditional methodology of the study as it has been developed, then the above problems will not be answered properly. Scientific studies in Islamic boarding schools should provide a greater portion for the development of Islamic studies with a Burhani style. Democracy can only be upheld by the enactment of the rule of law. Law has its logic and rationality, which can be developed by studying more ushul fiqh and manthiq. By synergizing the three reasons, Bayani, Burhani, and Irfani, pesantren will be able to face the demands of the times. For this reason, Islamic boarding schools need to formulate a more serious and systematic curriculum for Islamic studies by considering the respective portions of reasoning.